Semangat Perlawanan Musik Indie (Kasus Bali) - I Dewa Gede Kusuma (Institut Seni Indonesia Denpasar, 2018)
The experience of Serangan Island reclamation is a benchmark for the real failure of reclamation in the Southeast of Bali. The New Order (ORBA) situation during the time of President Soeharto was a separate Serangan Island with the cluster of Bali Island, and then there was a hoarding of coastal areas almost three times the initial area of Serangan Coast. Access to Attack can eventually blend without using a boat or boat. Indigenous peoples pasubayan in southern Bali, eager not to get hit by similar problems experience occurred in Serangan Island. Communities in south Bali are involved in resisting and resisting the reclamation plan through the practice of indie music peacefully, creatively, and without anarchism. This research is conducted by qualitative method in the context of critical culture study. The results show that environmental activists and indie musicians in Bali since 2012 are getting more agitated after the emergence of the issue of the Bay of Benoa reclamation plan. Indie musicians are slowly directing the ideology of their movement to reject the idea of government and developer investors to reclaim the Benoa Bay area of 838 Ha in Tanjung Benoa, Jimbaran, Badung regency, Bali. Indie music has a counter-interest in conveying the social message of the real conditions that occur in society. Indie music movements collaborate with activists and indigenous peoples in conveying resistance messages as an effort to protect Bali's natural environment in the future.